A novel powder formulation of coconut inflorescence sap inhibits alcoholic liver damage by modulating inflammatory markers, extracellular matrix metalloproteinase, and oxidative stress. Issue 5 (26th March 2018) - Jose, Svenia P.; Mohanan, Ratheesh; S, Sandya; S, Asha; IM, Krishnakumar
Abstract: Despite the fact that unfermented coconut inflorescence sap (CSP) is a popular health drink in many of the Asian countries, systematic investigations on its pharmacological effects are limited. Herein, we report the hepatoprotective effect of a novel powder formulation of CSP for the first time. Adult male Wistar rats were grouped into three and treated separately with vehicle, ethanol, and ethanol + CSP (250 mg/kg body weight) for 30 days. Ethanol treatment (12.5 g/kg body weight of 90% [v/v]) induced significant liver damage as evidenced from the elevation ( p < .01) in liver function markers (SGPT, SGOT, and ALP), inflammatory markers (WBC, CRP, IL‐6, TNF‐α, TLR‐4, and nitrite) and lipid peroxidation along with decrease in endogenous antioxidant markers (SOD, CAT, GPx, GSH) and significant dysregulation of extracellular matrix as shown by the over expressions of matrix metalloproteinase (MMP‐2, MMP‐9), and histopathology/cytology measurements. But, supplementation of CSP demonstrated significant ( p < .001) inhibition of alcoholic hepatic damage with reversal ( p > .05) of the biochemical markers and indicated hepatic cell regeneration. Practical applications: The results of the present study suggest plausible hepatoprotective efficacy of the powder form of coconut inflorescence sap (CSP) by modulating inflammatory markers, extracellular matrix metalloproteinase, and oxidative stress. Further, the stable powder form has great potential since it can overcome the inherent problem of rapid fermentation of the sap to alcohol during storage, which is a major hurdle in its development as a functional food/beverage.